Efeito genoprotetor in vitro de β-glucanas sobre linfócitos de frangos (Gallus gallus domesticus) expostos à aflatoxina B1 - Zimmermann, Carine Eloise Prestes (2013)
The aflatoxin B1 (AFB1) is one of the main mycotoxins that can be identified in foods, and has relevance for agricultural economics and public health because of its immunotoxic properties. A functional immune system is a basic requirement for a healthy life in modern animal production. The interaction involving nutrition and immunity is a strategic factor to obtain a high quality performance in the poultry industry. Immunomodulators such as β-glucans have an immunostimulating activity, which enables the host ability to resist opportunistic infections. To contribute to the elucidation of the mechanism of action of β-glucans in broiler chicken lymphocytes, the effects of the concentrations of 0.1, 1 and 10% of β-glucans derived from Saccharomyces cerevisiae were investigated in lymphocytes exposed to increasing concentrations of AFB1 (0, 0.1, 1, 10, 20 μg/ml). Lymphocytes were separated by Ficoll-Histopaque density and cultured in 96 well-plates containing AFB1 and/or β-glucans in a 5% CO2 atmosphere at 39°C. MTT, PicoGreen® and 2'-7'-dichlorofluorescein diacetate cytotoxicity tests were evaluated at 24, 48 and 72 h of incubation. The comet assay to elucidate the DNA damage was also performed. The percentage of viable cells decreased in the presence of 10 μg/ml AFB1 at 48 h (p < 0.05) and 10 and 20 μg/ml AFB1 at 72 h (p < 0.001 and p < 0.01, respectively), when compared to the control group (0 μg/ml). Furthermore, an increase in cell-free DNA in AFB1 concentrations > 1 μg/ml (p < 0.001) and the generation of ROS at 24 h were also observed. DNA damage increased approximately 2.3 fold in lymphocytes exposed to 20 μg/ml of AFB1 when compared to the control group. Conversely, β-glucans showed cytoprotective effects (p < 0.001), and the concentration of 1% reverted the AFB1-induced lymphocyte damage. β-glucans at 10% significantly increased (p < 0.001) the formation of reactive oxygen species (ROS), potentiating the AFB1-induced ROS formation. In conclusion, this study showed that AFB1 and β-glucans exert influence on lymphocyte oxidative metabolism and have dose-dependent potentiating effects. The results also showed genoprotective in vitro effect of β-glucans in poultry lymphocytes exposed to AFB1, being the concentration of 1% β-glucans able to maintain DNA integrity.